Private equity in Germany: An assessment of transaction, structures and players - Christoph Scheuplein (Hans-Böckler-Stiftung, 2022)
Since the last global financial crisis, private equity activities have increased again in Germany. This article provides an overview of developments between 2012 and 2018 from an employee perspective. It shows, among other things, the volume and sectoral focus of company takeovers, the new owners after the exit of the financial investors, and the proportion of companies in which parity co-determination is practised. It also examines the most active private equity companies, their funds, their returns and their use of tax havens.
Keywords: 330; co-determination; buy-out; company takeovers; financial investor